Efektivitas dan kontribusi pajak daerah serta retribusi daerah terhadap pendapatan asli daerah Kota Malang sebelum dan sesudah Covid-19 - Nurjihan, Mumtazah; Lailiyah, Hasanatul; Rahmawati, Anis Tri; Abdillah, Mochammad Nizar (Maliki Interdisciplinary Journal, 2024)
With this research, it is expected to be able to assess how effective and to what extent the role of taxes and fees that have an impact on revenue in Malang City before and after the emergence of Covid-19. The research method used is descriptive quantitative with secondary data. The data in this article were obtained through the report of the Regional Revenue Agency (Bapenda) of Malang City for the period 2019-2022. The research findings state that the effectiveness of local taxes and PAD decreased during the Covid-19 pandemic, while the effectiveness of local levies increased. The role of Malang City taxes influencing PAD in 2019-2022 is in the very good category, although it decreased during the Covid-19 pandemic in 2020. On the other hand, the role of local levies influencing PAD in the same period is in the very lacking category, although it increased during the Covid-19 pandemic in 2020.